1998
DOI: 10.1016/s0014-5793(98)00110-0
|View full text |Cite
|
Sign up to set email alerts
|

Presence of leptin receptors in rat small intestine and leptin effect on sugar absorption

Abstract: Leptin is involved in food intake and thermogenesis regulation. Since leptin receptor expression has been found in several tissues including small intestine, a possible role of leptin in sugar absorption by the intestine was investigated. Leptin inhibited D-galactose uptake by rat small intestinal rings 33% after 5 min of incubation. The inhibition increased to 56% after 30 min. However, neither at 5 min nor at 30 min did leptin prevent intracellular galactose accumulation. This leptin effect was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
84
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 31 publications
12
84
0
2
Order By: Relevance
“…Lostao et al (1998) demonstrated that leptin has a rapid inhibitory effect on -galactose uptake in the rat intestinal mucosa in vitro. In the same year, Morton et al (1998) showed that leptin can reduce the transcription of genes responsible for apolipoprotein biosynthesis (APO-AIV) in the enterocytes in mouse jejunum in response to olive oil administration.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Lostao et al (1998) demonstrated that leptin has a rapid inhibitory effect on -galactose uptake in the rat intestinal mucosa in vitro. In the same year, Morton et al (1998) showed that leptin can reduce the transcription of genes responsible for apolipoprotein biosynthesis (APO-AIV) in the enterocytes in mouse jejunum in response to olive oil administration.…”
Section: Figurementioning
confidence: 99%
“…accumulation indirectly through a local mechanism in the small intestine controlling the absorption of nutrients (Lostao et al 1998, Morton et al 1998 or intestinal motility (Woliński et al 2001). Lostao et al (1998) demonstrated that leptin has a rapid inhibitory effect on -galactose uptake in the rat intestinal mucosa in vitro.…”
Section: Figurementioning
confidence: 99%
“…The functional OB-R is predominantly expressed in the jejunum and more weakly in the ileum, the two major sites that are involved in nutrient handling. In this context, it has been shown that leptin produced a rapid inhibitory effect on sugar absorption in rat intestinal rings [68]. Likewise, leptin causes a rapid activation of STAT5 in jejunum, which is associated with a reduction of the apolipoprotein-AIV transcript expression 90 min after ingestion of a pure fat load [67].…”
Section: Leptin Action On Gutmentioning
confidence: 99%
“…In the juvenile rat, leptin receptor expression has been found in several tissues including small intestine (Lostao et al, 1998). In mice, expression of the functional isoform leptin receptor is restricted to the jejunum and is readily detected in isolated enterocytes from this site by the RT-PCR technique (Morton et al, 1998), suggesting that the epithelium of the jejunum is a direct target of leptin action.…”
Section: Leptin Function In the Juvenile Gutmentioning
confidence: 99%
“…In mice, expression of the functional isoform leptin receptor is restricted to the jejunum and is readily detected in isolated enterocytes from this site by the RT-PCR technique (Morton et al, 1998), suggesting that the epithelium of the jejunum is a direct target of leptin action. Indeed, Lostao et al (1998) have originally demonstrated that leptin has a rapid inhibitory effect on sugar absorption in the rat intestinal mucosa in vitro. In their study, leptin inhibited D-galactose uptake by rat small intestinal rings, respectively by 33 and 56% after 5 and 30 min of incubation!…”
Section: Leptin Function In the Juvenile Gutmentioning
confidence: 99%